Perancangan Sistem Start Engine Dan Keamanan Sepeda Motor Menggunakan Arduino Uno Berbasis Android - Nahrowi; Perani Rosyani (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
In today's technological advances, people have used motorized vehicles, one of which is a motorbike as a means of transportation in everyday life as a facility for activities such as work. However, the motorcycle security system currently still uses conventional locks that are easily damaged by thieves in a short time which can result in material and non-material losses for motorcycle owners. One of the automotive technologies that can increase the comfort and convenience of motorcycle users is by introducing a more sophisticated and easy engine start and motorcycle safety system through an Android smartphone. The system development method used in this study is the waterfall method. This development model is linear from the early stages of system development, namely the planning stage to the final stage of system development, namely the maintenance stage. The purpose of this research is to design a tool using the Arduino Microcontroller to control the Start Engine and Motorcycle Alarm, create an android application that functions as a remote to control the Start Engine and Motorcycle Alarm, increase motorcycle security with an alarm as a security system, make it easier when looking for motorbikes in the parking area with an alarm and increasing the ease and comfort of users in operating motorbikes. From the results of this study it is hoped that the application can make it easier for users to control motorized vehicles such as motorbikes via an Android smartphone.